2020
DOI: 10.3389/fcomm.2020.519955
|View full text |Cite
|
Sign up to set email alerts
|

The Margins of the Language Network in the Brain

Abstract: This review paper summarizes the various brain modules that are involved in speech and language communication in addition to a left-dominant "core" language network that, for the present purpose, has been restricted to elementary formal-linguistic and more or less disembodied functions such as abstract phonology, syntax, and very basic lexical functions. This left-dominant perisylvian language network comprises parts of inferior frontal gyrus, premotor cortex, and upper temporal lobe, and a temporoparietal int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 365 publications
(390 reference statements)
3
80
0
Order By: Relevance
“…In sum, the activation for the unknown language relative to the native language monitoring is associated with differences in phonological, lexical, syntactic, and semantic processing, as well as to the processing of the different prosodic features of Japanese. fMRI studies on prosody found right-literalized activation in the superior temporal, dorsolateral, and medial frontal, insular/fronto-opercular cortex, and cerebellum [42].…”
Section: Discussionmentioning
confidence: 98%
“…In sum, the activation for the unknown language relative to the native language monitoring is associated with differences in phonological, lexical, syntactic, and semantic processing, as well as to the processing of the different prosodic features of Japanese. fMRI studies on prosody found right-literalized activation in the superior temporal, dorsolateral, and medial frontal, insular/fronto-opercular cortex, and cerebellum [42].…”
Section: Discussionmentioning
confidence: 98%
“…For both HF & LF, activity in the right Anterior Temporal Lobe (rATL) is observed. Anterior temporal lobes are generally involved in social cognition, theory of mind processing, social conceptual knowledge, semantic integration, and memory systems that are linked to reward and valence [49,22].…”
Section: High and Low Context Familiarity Engages Different Brain Regionsmentioning
confidence: 99%
“…Furthermore, we observed connectivity in ATL regions for both high-familiar and less-familiar context stimuli. Anterior temporal lobes are generally involved in social cognition, theory of mind processing, social conceptual knowledge, and memory systems that are linked to reward and valence [22]. ATL is reported as the multimodal integration hub, which integrates information from different modal-ities, including internal body physiology, exteroceptive sensations, motivation and hedonic input, and social cognition to represent the context-sensitive conceptual knowledge and semantic meaning.…”
Section: Differential Processing Of Higher-order Regions For High and Less Context Familiaritymentioning
confidence: 99%
“…Historically, language functions in the brain have been assigned, to ''Broca's'' and ''Wernicke's'' areas, areas connected via the arcuate fasciculus (Geschwind, 1970). Subsequently, updated models of the language network have been established, comprising various areas in the temporal lobe, inferior frontal gyrus (IFG), premotor, sensorimotor, supplementary motor, and temporoparietal cortex (Hickok and Poeppel, 2007;Hickok, 2009;DeWitt and Rauschecker, 2012;Poeppel et al, 2012;Bornkessel-Schlesewsky et al, 2015;Hertrich et al, 2016Hertrich et al, , 2020Skeide and Friederici, 2016). These areas are interconnected via dorsal and ventral pathways and the frontal aslant tract, with distinct functions each (Dick et al, 2014).…”
Section: Introductionmentioning
confidence: 99%